Emergency Management For Chest trauma : Collaborative Efforts Among Nursing, Chest, Medicine and Laboratory Diagnosis - Huda Abdulrazaq Alsabi7, Adraa Ibrahim Alshoreet8, Huda Mohammed Ben Alsheikh9, Mustafa Ali Albarakat10, Ali Nassir Al Atafi11, Ali Ibrahim Alsaleh12,Fahad Ayesh Shutaywi alanazi13, Hayder Taher Al Humaid1, Zainab Taher M Alhumaid2, Jaber Ali Al Abdullah3, Abdullah Mohammed Alshakes4, Yousef Yassen Salman Alhashim5, Majid Abdullah Alwasaibai6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Chest trauma is a significant cause of morbidity and mortality, often requiring a multidisciplinary approach for optimal management. Initial evaluation follows Advanced Trauma Life Support (ATLS) protocols, with high flow oxygen, ECG monitoring, and large-bore IVs. Diagnostic tools include chest radiography, ultrasound, CT, and laboratory tests assessing hemoglobin, electrolytes, and coagulation status. Nurses play a vital role in airway and breathing management, hemodynamic monitoring, pain control, and complication prevention. Pulmonary/critical care and thoracic surgery specialists guide operative interventions, ventilation management, and strategies to avoid complications such as retained hemothorax. Collaboration with specialists in chest medicine, surgery, and laboratory diagnosis is crucial in managing conditions such as pulmonary contusions, cardiac, esophageal, and diaphragmatic injuries. Early intervention and collaborative care can significantly reduce morbidity and mortality in chest trauma patients.